Innovation Strategy and Firm Performance An empirical study of publicly listed firms - Strecker, Nanja. (Gabler, 2009)
Even though innovation has become essential for firms long-term success, formulating an innovation strategy is far from common in companies and not yet well defined and understood in research. This dissertation outlines all dimensions of innovation strategy. Moreover, it answers the question, to what extent there is a relation between innovation strategy and firm performance. The comprehensive empirical research is based on 122 publicly listed manufacturing firms from around the world. It consists of primary research complemented with secondary data and capital market based financials, making the outcome highly reliable. The results of the study show a combination of choices needs to be done right for a firms innovation strategy to positively impact its performance. The innovation portfolio should include more radically new projects; they are rewarded. Forces of marketers and R&D people need to be joined to ensure new products relevant to customers. All innovation efforts should be focused in a few areas in order to benefit from focus and synergies.